2006
DOI: 10.1007/s10826-006-9028-y
|View full text |Cite
|
Sign up to set email alerts
|

After-School Supervision, Psychosocial Impact, and Adolescent Smoking and Alcohol Use in China

Abstract: We examined effects of self-care after school hours and psychosocial factors on cigarette smoking and alcohol use among adolescents in China. Survey data were obtained from 4734 7th and 11th grade students from seven cities across China. Students were queried about the frequency and quantity of unsupervised self-care after school in an average week. Tobacco and alcohol usage were also obtained. Odds ratios were calculated to determine the strength of association between unsupervised self-care after school and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Adolescents reporting a low level of family functioning were at a significantly increased risk for frequent alcohol and marijuana use than those with a high level. This finding is consistent with previous research on family-substance use association, in that parents' drug use, dysfunctional family structure, lack of parental support, and parent-child communications are strongly associated with adolescents' tendency to experiment with substance use (Barrett & Turner, 2006;Sussman et al, 1993;Weiss, Liu et al, 2006). While we acknowledge the powerful impact of peer influence on adolescent substance use, our study further confirmed that family functioning and parental influence play independent roles in adolescent substance use.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adolescents reporting a low level of family functioning were at a significantly increased risk for frequent alcohol and marijuana use than those with a high level. This finding is consistent with previous research on family-substance use association, in that parents' drug use, dysfunctional family structure, lack of parental support, and parent-child communications are strongly associated with adolescents' tendency to experiment with substance use (Barrett & Turner, 2006;Sussman et al, 1993;Weiss, Liu et al, 2006). While we acknowledge the powerful impact of peer influence on adolescent substance use, our study further confirmed that family functioning and parental influence play independent roles in adolescent substance use.…”
Section: Discussionsupporting
confidence: 92%
“…Parental nurturance has been identified as a salient influence on early adolescent alcohol use, while deficits in parental support have been linked both cross-sectionally and prospectively to a number of problem behaviors in adolescents, including adolescent substance abuse (Barnes, Reifman, Farrell, & Dintcheff, 2000;Korhonena, Huizinkc, Dick, Pulkkinene, Rosca, & Kaprio, 2008;Simons-Morton, 2007). Parental monitoring has been shown to be a protective factor against several problems in adolescence both cross-sectionally and longitudinally, with higher levels of parental monitoring being associated with lower levels of alcohol use and reduced odds for onset of heavy drinking and other drug use (Barnes et al, 2000;Lochman, Wells, & Murray, 2007;Weiss, Liu, Sussman, Unger, Cen, Chou, et al, 2006). Explicit parental disapproval of substance use has been associated with decreased alcohol and drug involvement in early adolescence in several studies (Barnes & Welte, 1986;Dielman, Butchart, & Shope, 1993;Hyatt & Collins, 2000).…”
Section: Family Functioning and Adolescent Substance Usementioning
confidence: 99%
“…After that, a composite score for emotional well-being was computed using participants’ standardized scores on positive affect and self-esteem; a composite score for emotional distress was computed using participants’ standardized scores on depression, anxiety, and negative affect. The measures have been demonstrated decent reliability and validity in Chinese adolescents (Li & Lopez, 2007; Li et al, 2017; Weiss et al, 2006). In the current study, the Cronbach’s αs for emotional well-being and emotional distress were .93 and .93, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, more days not under the supervision of a guardian after school during early adolescence increased the risk of early established smoking. After-school supervision and the degree of self-care are associated with the risk of adolescent tobacco use [ 33 , 34 ]. A randomized controlled trial showed that voluntary after-school programs may prevent alcohol use among early adolescents by promoting positive social development [ 35 ].…”
Section: Discussionmentioning
confidence: 99%